Gambaran Asupan Protein dengan Kadar Hb pada Penderita Gagal Ginjal Kronik yang Mendapat Perawatan Hemodialisa di Unit Hemodialisa - Risya ocfianella; Sufiati Bintanah; Erma Handarsari (Jurnal Gizi, 2017)
Chronic renal failure is a decline in kidney function is quite heavy going slowly (chronic) caused by kidney disease. Is progresive and generally can not be recovered. Therapy in chronic renal failure including dialysis and kidney transplantation. Dialysis therapy is often done perotonial hemodialysis and dialysis. Hemodialysis is a form of dialysis is performed in end – stage renal disease. Patients chronic renal failure with hemodialysis are given high-protein diet provided 50 % of them have a high biological value that sufficient levels of essential amino acids. Disorders of protein metabolism in chronic renal failure usually leads to decreased levels of Hb, so that thehigh protein diit was made compulsory to the patients with chronic renal failure with hemodialysis treatment. The general objective is reviewing image with high levels of Hb protein intake in patients chronicrenal failure with hemodialysis in the inpatient hospital PKU Muhammadiyahyogyakarta. While the goal is to describe the particular characteristics and describing the protein intake, describing the Hb levels, and decribing  the protein intake with Hb levels of patients with chronic renal hemodialysis. Types of data used are primary and secondary data. Primary data through interviews with patients and their families include medical history, eating habits at homeand food intake during hospitalization. To find their food intake using the recall, while the secondary data through patient medical records. The results shows the characteristic of patients cronic renal failure with hemodialysis is largely male-sex. The lowest age of them is 46 years and the highest is 70 years. The average of protein intake is adequate (34 – 44 gr/days), while the big part of them have Hb levels from 7 to9.9 mg/dl.Keywords : protein, Hb, renal chronic failure, haemodialysis